2007
DOI: 10.1111/j.1472-765x.2007.02257.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cryptosporidium oocysts in fresh and frozen cattle faeces: comparison of three methods

Abstract: Aims:  The aim of this study was to compare the performance of three commonly used screening tests for Cryptosporidium oocysts in fresh and frozen cattle faeces. Methods and Results:  Twenty‐nine freshly voided faecal samples were collected from calves from three farms in the northwest of England. Three diagnostic tests for Cryptosporidium were carried out on each sample both before and after freezing – the modified Ziehl‐Neelsen (MZN) and auramine phenol (APh) stains and a commercial enzyme immunoassay (EIA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 35 publications
3
20
0
5
Order By: Relevance
“…However, the analytical results of this study are consistent with studies that analyzed stool samples from diverse domestic species by both staining techniques, finding no significant differences in sensitivity (De Quadros et al 2006, Brook et al 2008. In the case of water, one study analyzed samples of wastewater treatment plants for the detection of Cryptosporidium spp.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…However, the analytical results of this study are consistent with studies that analyzed stool samples from diverse domestic species by both staining techniques, finding no significant differences in sensitivity (De Quadros et al 2006, Brook et al 2008. In the case of water, one study analyzed samples of wastewater treatment plants for the detection of Cryptosporidium spp.…”
Section: Resultssupporting
confidence: 79%
“…The main advantages of ZN staining are that it is inexpensive and the slides can be kept as permanent records, whereas slides with AU stain cannot (Brook et al 2008). Moreover, AU requires an expensive fluorescence microscope and background fluorescence could be a problem in AU-stained smears if there is a lot of fecal debris (Weber et al 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Arrowood and Sterling (1989) also reported problems with false-positive results using acid-fast staining techniques, and some fungal spores have been found to be acid-fast (Casemore, 1991;Sunnotel et al, 2006). A study that compared three methods of detecting Cryptosporidium oocysts in cattle feces (mZN, auramine phenol staining and a commercial enzyme immunoassay kit), found that although mZN had a comparable or better sensitivity than the other methods, the specificity was lower (Brook et al, 2008), and the main advantages of this method, according to these authors, were its price and the ease of keeping the slides as a permanent record.…”
Section: Discussionmentioning
confidence: 99%
“…For instance a sample could be considered positive if five oocysts or more were observed, causing low-level shedding of oocysts to become interpreted as negative samples [27]. This extra loss of sensitivity in turn could be resolved by using repeated stool sample examinations on consecutive days [28]. The modified Ziehl-Neelsen staining is a low cost technique (about 0,15 US$ per sample), while the cost for PCR-based diagnosis is considerably higher (about 7,60 US$ per sample) [29].…”
mentioning
confidence: 99%